Adjustments to the Annotated zoogeography of non-marine Tardigrada. Part III: North America and Greenland by Kaczmarek, Michalczyk & McInnes (Zootaxa 4203) - Miller, William R.; Perry, Emma S. (Zootaxa, 2019)
The art of biogeography starts with two basic questions: WHERE has each species been found and WHICH species have been found there. While using the Annotated zoogeography of non-marine Tardigrada. Part III: North America and Greenland (Kaczmarek, et al. 2016) we found that 26 non-standard state and province abbreviations had been used in the WHERE table and that there was no WHICH table. We present an adjusted WHERE table and add a WHICH table as a supplement to the original paper.